Discussion on tbe Key Problems in tbe Application of SDN Tecbnology in Telecommunication Network - Zhonghua Chen; Chengbin Shen; Jianping Zhang (Dianxin kexue)
Through the analysis on the architecture of SDN technology, the key problems in four aspects of deploying SDN in traditional communication network were provided, including data path constructing, control plane constructing, application integration and smooth evolution. Also, according to mainstream solution, a method of deploying SDN in communication network was given.